Sistem Kendali Dan Monitoring Dengan Syaraf Tiruan Pada Pembangkit Listrik Tenaga Surya - Hengki Sikumbang; Abdul Haris; Muhammad Jafar Elly (PETIR, 2020)
The problem with the condition of the Solar Power Plant is still not optimal due to position of the solar cells in generator is still static so that absorption of light is still not even though Hybrid technology is now available but cannot be optimized properly and still cannot be optimized implemented especially in small scale and remote areas. Another problem that needs attention is the continued operation of installed Solar Power Plants (SPPs), considering the installation and maintenance of the plant requires high investment costs because the installation of solar panels requires a large amount of land and costs besides requiring qualified technical personnel to handle problems and monitoring plant conditions are needed quickly and accurately. From the description of the problem, the first step is to identify the technology used in the factory, the second is the need to design a new system to be able to solve important problems in the plant and the third is to build a computerized system that uses the Hybrid Method on the plant used. is a combination of Artificial Intelligence and Data Mining Processes so that it can present accurate data so that it can help and analyze plant performance, monitor and control plants remotely quickly by using Web Control.